Strategi Pengembangan Usaha Bandeng Duri Lunak Mandala Presto Berbasis Model Bisnis Kanvas Di Kabupaten Bogor - Dasairy, Zulfa Sania; Hubeis, Musa; Muhandri, Tjahja (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
Mandala Presto is one of the milkfish processing businesses in Bogor Regency. The business started producing soft-boned milkfish without packaging in 2011. Collaborating with 35 street vendors, they sold soft-boned milkfish in traditional markets and through door-to-door sales. In 2018, the owner changed the business model to focus on hygienic vacuum-packaged soft-boned milkfish. The aims of this study were (1) to identify internal and external factors influencing the development of Mandala Presto's soft-boned milkfish business, (2) to develop the implementation of Mandala Presto's soft-boned milkfish business model canvas for its business strategy, and (3) to determine the prioritized strategy choices from the nine elements of the business model canvas to enhance the growth of Mandala Presto's soft-boned milkfish business. The method used was the business model canvas to map the condition of Mandala Presto, followed by descriptive and quantitative analysis including the internal factor evaluation (IFE) matrix, external factor evaluation (EFE) matrix, internal-external (IE) matrix, strengths, weaknesses, opportunities, and threats (SWOT) matrix, and analytical hierarchy process (AHP) for business model improvement. The IFE calculation result is 3.32, and the EFE calculation result is 2.79, which are mapped in the IE matrix in cell IV, indicating that the business is in a growing and developing position. The priority strategy determination with AHP focuses on four elements of the business model canvas: key partners, key activities, channels, and key resources.